2002
DOI: 10.1016/s1074-5521(02)00282-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Dependent DNA Dynamics by Scanning Force Microscopy Time-Resolved Imaging

Abstract: Scanning force microscopy was used to study in fluid the conformational fluctuations of two double-stranded DNA molecules resulting from differently cut pBR322 circular DNAs. A new approach was conceived to monitor the thermodynamic equilibrium of the chain dynamics on different scale lengths. This method made it possible to demonstrate that both the observed DNA molecules were allowed to equilibrate only on their local small-scale dynamics during the time of the experiment. This capability of monitoring the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…We found that even though WLL behave on large scales as BRW, as expected, the effective step size of this BRW is larger than that calculated from the local persistence length of the loop. This new prediction can in principle be directly tested by experiments on double stranded DNA loops that can monitor both local (persistence length) and global (e.g., radius of gyration) properties of the polymers (see, e.g., [14][15][16]). It would be interesting to test these results and predictions against Monte Carlo simulations along the lines of [17] (where worm-like chain is modelled as the set of short straight segments with torsional and bending angles properly chosen to approach the smooth limit).…”
mentioning
confidence: 99%
“…We found that even though WLL behave on large scales as BRW, as expected, the effective step size of this BRW is larger than that calculated from the local persistence length of the loop. This new prediction can in principle be directly tested by experiments on double stranded DNA loops that can monitor both local (persistence length) and global (e.g., radius of gyration) properties of the polymers (see, e.g., [14][15][16]). It would be interesting to test these results and predictions against Monte Carlo simulations along the lines of [17] (where worm-like chain is modelled as the set of short straight segments with torsional and bending angles properly chosen to approach the smooth limit).…”
mentioning
confidence: 99%
“…In our experience (Nagami et al, 2002;Scipioni et al, 2002;Zuccheri et al, 1998), AFM imaging in liquid is feasible and useful, but not simple. The huge amount of good-quality images that are necessary to attempt a quantitative characterization of the RNA secondary structures would require an almost prohibitive effort if the imaging was performed under liquid.…”
Section: Possible Experimental Improvementsmentioning
confidence: 98%
“…17 This scale of rigidity was supported by the analysis of DNA sequences we carried out on AFM images. [42][43][44][45] Assuming first-order elasticity, we evaluated the elastic contributions to the partition functions, related to the sum of the bending, DE b (k), and twisting, DE t (k), energies necessary to distort the kth free DNA tract assumed as the standard state in the nucleosomal form.…”
Section: Cn Amentioning
confidence: 99%
“…41 Finally, the curvature and flexibility functions calculated adopting the dinucleotide step orientational parameters proposed in previous papers were successfully compared with experimental average curvature and related dispersion of DNA tracts we directly obtained from the statistical analysis of Atomic Force Microscopy images of DNA tracts. [42][43][44][45] Because of the little variance of the orientational angles, it is convenient to adopt a representation of the curvature as a vector in the complex plane, corresponding to the first-order Taylor expansion of the pertinent rotation matrix product 38 …”
Section: Introductionmentioning
confidence: 99%